2019
DOI: 10.1111/1756-185x.13663
|View full text |Cite
|
Sign up to set email alerts
|

Performance of SLE responder index and lupus low disease activity state in real life: A prospective cohort study

Abstract: Objective To prospectively assess the performance of the systemic lupus erythematosus (SLE) responder index (SRI) and the lupus low disease activity state (LLDAS) in a cohort‐based, “real‐life” clinical setting. Methods One hundred and thirty‐one consecutive patients with SLE were subdivided into two groups based on the need or not to escalate their immune suppressive treatment. Clinimetrics including physician global assessment scale (PGA), SLE Disease Activity Index 2000 (SLEDAI‐2K), European Consensus Lupus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…Consistent with previous studies, we observed that the achievement of a stable remission might protect from late flares and eventually damage [15,17,28,32,33]. Notably, we also confirmed that LLDAS largely overlaps with clinical remission [15] and might constitute a feasible treatment endpoint both in clinical trials and routine rheumatology practice [26,34,35]. In line with other reports, we also found that the musculoskeletal system was most frequently involved in late flares and more prone to be involved in damage accrual [27,29].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we observed that the achievement of a stable remission might protect from late flares and eventually damage [15,17,28,32,33]. Notably, we also confirmed that LLDAS largely overlaps with clinical remission [15] and might constitute a feasible treatment endpoint both in clinical trials and routine rheumatology practice [26,34,35]. In line with other reports, we also found that the musculoskeletal system was most frequently involved in late flares and more prone to be involved in damage accrual [27,29].…”
Section: Discussionsupporting
confidence: 92%
“…Despite this, only 17% of patients felt that the pandemic had a detrimental impact on their disease. Indeed, the reported annual rate of patients needing treatment escalation at least once was 29%, which is stable compared to the pre-pandemic setting [ 40 ]. The all-cause annual hospitalisation rate in this study was 9.6/100 person-years, which is also consistent with our preliminary observations during the first pandemic wave [ 21 ] and previous evidence in the literature from non-pandemic settings [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 Regarding patients with SLE, clinical, laboratory, and treatment features at time of enrollment were collected through a dedicated in-house software as previously described. 24 Disease activity was measured by using the SLE Disease Activity Index 2000 (SLEDAI-2K). 25 The Lupus Low Disease Activity State (LLDAS) was used as a surrogate of remission.…”
Section: Methodsmentioning
confidence: 99%